Pengaruh Lima Kepribadian Besar Terhadap Kreativitas dan Implikasinya pada Kinerja Anggota Masyarakat Surabaya Pecinta Amphibi dan Reptil - Risa Watti; Djojo Dihardjo; Nurul Azizah (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This study analyzed the influence of five large personality dimensions—extraversion, friendliness, openness, caution, and emotional stability—on creativity and its implications on the performance of members of the amphibian and reptile-loving community in Surabaya. Using the quantitative approach and Likert questionnaire, the study found that openness and extraversion had a significant positive effect on creativity, which had an impact on improving the performance of community members. High creativity supports innovation in preservation, care, and education. These results suggest the importance of personality character management to encourage creativity and community effectiveness.